Effect of cutting length on the asexual propagation of tacaco (Sechium tacaco; Cucurbitaceae) (UNED Research Journal, 2024)
Introduction: There is few information on the vegetative propagation of tacaco (Sechium tacaco). Objective: To evaluate the effect of cutting length on the asexual propagation of tacaco. Methods: We carried out the test in Ujarrás, Cartago, Costa Rica. We use 36 cuttings from secondary shoots, of three different lengths (long, medium and short; 12 cuttings of each length). We treated the cuttings with 10 000ppm IBA, and kept them under greenhouse conditions for 41 days. Then we transplanted them into plastic bags, and kept them under a shade house for 27 days. We evaluated the following variables: root dry weight, aerial part dry weight, aerial part dry weight/root dry weight ratio, change in height, change in number of nodes, change in number of shoots, and change in stem thickness. Results: We did not find significant differences between treatments for any of the evaluated variables. Conclusion: The length of the cutting did not significantly influence the vegetative propagation of tacaco.
Keywords: Curcubitaceae; clone; rooting; Central America; vegetable